The western extension of the Balantak Fault revealed by the 2021 earthquake cascade in the central arm of Sulawesi, Indonesia - Andrean V. H. Simanjuntak; Kadek H. Palgunadi; Pepen Supendi; Umar Muksin; Endra Gunawan; Sri Widiyantoro; Nicholas Rawlinson; Mudrik R. Daryono; D. Daryono; Dwikorita Karnawati; Nuraini R. Hanifa; Cecep Pratama; et al. (Geoscience Letters, 2024)
Abstract Two shallow earthquakes of moment magnitude 6.2 and 5.8 occurred in the central arm of Sulawesi on 26 July 2021 and 26 August 2021, respectively. The fault responsible for the earthquake had previously only been partially mapped, thus making further analysis of its characteristics crucial for the assessment of seismic hazard. In this study, we exploit data from a regional seismic network, relocate the associated seismicity using the double difference method with an updated velocity model, determine focal mechanisms from full-waveform inversion, and analyze the static stress changes caused by the mainshock. Our relocated hypocenters and focal mechanism solutions reveal two earthquake clusters, one at the Central Balantak Fault that exhibits normal slip on a SE–NW trending rupture, and the other at the West Balantak Fault, which exhibits dextral strike-slip motion on a SE–NW trending rupture. The additional static stress increase transferred by the Mw 6.2 mainshock may have triggered the subsequent Mw 5.8 event. A detailed assessment of previously unmapped faults in Central Sulawesi is essential for a more comprehensive understanding of seismic hazard in the region.